Understanding the Links Between the Climate Crisis and Child Health - Yakup Gözderesi; Enis Hikmet Özmert (Çocuk Dergisi)
Climate change has severe adverse effects on both child and adult health. It affects multiple body systems including the respiratory, immunologic, and neurologic systems. Increased temperatures, water and food insecurity, extreme climate events such as heatwaves and a loss of biodiversity all increase the prevalence of infectious and non-communicable disease. ISSOP is an international organization that works with social pediatrics and child health professionals in areas of health promotion, disease prevention, curative pediatrics and rehabilitation through participation in system development, policy-making processes and the publishing of international documents for guidance. The “Responding to the Impact of Climate Change on Children” webinar series is a global initiative that aims to highlight the importance of climate change and its adverse effects on child health. Eight structured two-hour webinars were held between February and September 2021. In this review, we aim to summarize the topics of the webinar series and provide recommendations to child health professionals which they can use in their academic and clinical practices. The consequences of climate change on health and, more specifically, child health, deepening inequalities and inequities, the essential role of youth, and the integration of climate change into health education will be discussed. Climate change is a public health emergency and requires everyone to take action. Healthcare professionals, as members of a respected and trusted occupation, must be made aware of the negative health consequences of climate change and play an informative role in society. The impact of such consequences that affect children’s health can be mitigated by increasing societal awareness of the effects of climate change, taking the relevant precautions and implementation of mitigation and adaptation strategies by parents and pediatricians.